The Impact of Islamic Financial Inclusion on Gender Inequality Reduction in Indonesia - Muhammad Syarif H Djauhari; Rifadli D Kadir; Chitra Yuliashri Katili; Edo Segara Gustanto; Luthfia Ayu Karina; Selfia Bintariningtyas; Yeni Puspita (Journal of Islamic Economics and Finance Studies, 2026)
This study examines whether Islamic financial inclusion contributes to reducing gender inequality across 33 Indonesian provinces during 2018–2023. Using a balanced panel of 198 observations, the Islamic Financial Inclusion Index was constructed through Principal Component Analysis based on accessibility, availability, and usage. At the same time, gender inequality was measured using the provincial Gender Inequality Index. Panel-model selection identified the Common Effect Model as the most appropriate specification. The results reveal regional disparities in Islamic financial inclusion, with DKI Jakarta, Aceh, and West Nusa Tenggara recording the highest levels, while East Nusa Tenggara remained the least inclusive. More importantly, Islamic financial inclusion has a negative and statistically significant association with gender inequality, indicating that provinces with broader access to and use of Islamic financial services tend to exhibit lower gender inequality. These findings extend financial development theory by showing that the equalizing role of financial inclusion also operates within an Islamic financial framework. The study implies that policymakers and Islamic financial institutions should adopt gender-responsive strategies, strengthen women’s effective use of financial services, expand digital and financial literacy, and prioritize underserved provinces.   Studi ini meneliti apakah inklusi keuangan syariah berkontribusi dalam mengurangi ketimpangan gender di 33 provinsi di Indonesia selama 2018–2023. Dengan menggunakan data panel dari 198 pengamatan, Indeks Inklusi Keuangan Islam dibangun melalui Principal Component Analysis (PCA) berdasarkan aksesibilitas, ketersediaan, dan penggunaan. Pada saat yang sama, ketimpangan gender diukur menggunakan Indeks Ketimpangan Gender pada tingkat provinsi. Pemilihan model data panel mengidentifikasi Random Effects Model (REM) sebagai model yang paling tepat. Hasil penelitian ini mengungkapkan kesenjangan regional dalam inklusi keuangan syariah, dengan DKI Jakarta, Aceh, dan Nusa Tenggara Barat mencatatkan tingkat tertinggi, sementara Nusa Tenggara Timur tetap menjadi yang paling tidak inklusif. Lebih lanjut, inklusi keuangan Islam memiliki hubungan negatif dan signifikan secara statistik dengan ketimpangan gender, yang menunjukkan bahwa provinsi dengan akses dan penggunaan layanan keuangan Islam yang lebih luas cenderung memiliki ketimpangan gender yang lebih rendah. Temuan ini memperluas financial development theory dengan menunjukkan bahwa peran penyetaraan inklusi keuangan juga beroperasi dalam kerangka keuangan Islam. Studi ini menyiratkan bahwa pembuat kebijakan dan lembaga keuangan Islam harus mengadopsi strategi responsif gender, memperkuat penggunaan layanan keuangan yang efektif oleh perempuan, memperluas literasi digital dan keuangan, serta memprioritaskan provinsi yang kurang terlayani.